Multiomic analysis reveals decidual‐specific transcriptional programing of MAIT cells. (27th October 2021) - Vazquez, Jessica; Chavarria, Melina; Chasman, Deborah A.; Welch Schwartz, Rene; Tyler, Chanel T.; Lopez, Gladys; Fisher, Rachel C.; Ong, Irene M.; Stanic, Aleksandar K.
Abstract: Problem: Mucosal‐Associated Invariant T (MAIT) cells have been recently identified at the maternal‐fetal interface. However, transcriptional programming of decidual MAIT cells in pregnancy remains poorly understood. Method of study: We employed a multiomic approach to address this question. Mononuclear cells from the decidua basalis and parietalis, and control PBMCs, were analyzed via flow cytometry to investigate MAIT cells in the decidua and assess their transcription factor expression. In a separate study, both decidual and matched peripheral MAIT cells were analyzed using Cellular Indexing of Transcriptomes and Epitopes by Sequencing (CITE‐seq) coupled with gene expression analysis. Lastly, decidual MAIT cells were stimulated with E.coli and expression of MR1 by antigen presenting cells was measured to evaluate decidual MAIT cell function. Results: First, we identified MAIT cells in both the decidua basalis and parietalis. CITE‐seq, coupled with scRNA‐seq gene expression analysis, highlighted transcriptional programming differences between decidual and matched peripheral MAIT cells at a single cell resolution. Transcription factor expression analysis further highlighted transcriptional differences between decidual MAIT cells and non‐matched peripheral MAIT cells. Functionally, MAIT cells are skewed towards IFNγ and TNFα production upon stimulation, with E.coli leading to IFNγ production. Lastly, we demonstrate that MR1, the antigen presenting molecule restricting MAIT cells, is expressed by decidual APCs. Conclusion: MAIT cells are present in the decidua basalis and obtain a unique gene expression profile. The presence of MR1 on APCs coupled with in vitro activation by E.coli suggests that MAIT cells might be involved in tissue‐repair mechanisms at the maternal‐fetal interface.